(untitled) - Leblanc, Dee Ann (New Jersey, 2005)
Previous editions of Linux For Dummies have garnered rave reviews. However, there’s one scary term applied to them—outdated! The 6th Edition remedies that with easy-to-understand information on the latest version of the most popular Linux distributions, including Fedora Core, SuSE, Mandrake, Xandros, Linspire, and Knoppix. This guide walks you though installing, configuring, tuning, and using each version of Linux, the low-cost, secure alternative to expensive operating systems.
Keywords: Operating systems (computers),Linux